The church : the evolution of Catholicism - McBrien, Richard P. (New York, NY : HarperOne, 2008)
Reveals the evolution of the Church's relationship to the divine, its leadership of the faithful, and its role as a global religion.
Post-Vatican II ecclesiology: the church ad extra -- The church and the kingdom, or reign of God -- The church and the world -- The church and salvation -- Catholic social teaching -- The church and politics -- The church and liberation -- The church and the holy spirit -- Post-Vatican II ecclesiology: the church ad intra -- The church as a communion -- Authority in the church -- Reception -- Ministry -- An excursus on sacraments and liturgy -- Mary and the church -- Feminist and nonfeminist ecclesiology by Catholic women -- Hispanic and Latino/a ecclesiologies -- African and African American ecclesiologies -- New movements in the church -- The emerging world-church -- Brief summation -- The future of the church and its ecclesiologies -- Synthesis of the book -- Ten pastoral applications -- The future of the church and its ecclesiologies.
Includes bibliographical references (p. 467-471) and indexes.
Keywords: Catholic Church -- Doctrines -- History